SELECTED PARAMETERS AFFECTING THE SPEED OF CAR TRAFFIC IN GIS ENVIRONMENT (Perner's Contacts, 2010)
This paper deals with problematic of factors and parameters affecting the speed of cars on the roads. There were chosen the most important parameters, which can be properly modeled in GIS environment. The practical part is based on the testing of the chosen parameters in selected GIS software and creating the manual technique for computing of the average speed and time for drive of road segments.
Keywords: speed; road segment; parameters; car transportation; GIS